Make toons that sell without selling out! - Plympton, Bill 1946- (CRC Press, Taylor & Francis Group, 2022)
"Learn the secrets behind independent animation from the "King of independent Animation"--Academy Award-nominated Bill Plympton. This living legend breaks down how to make a career outside of the world of corporate animation--and without compromise. Learn time-saving techniques, the secrets to good storytelling, and the business-side of short and feature-length animation films"--
Keywords: Animation (Cinematography) / Vocational guidance; Animated films / Production and direction / Vocational guidance; Animation (Cinéma) / Orientation professionnelle; Lehrbuch